EFFECT OF ELECTRONIC CIGARETTE SMOKING AFTER TOOTH EXTRACTION ON THE INCIDENCE OF ALVEOLAR OSTEITIS - Danang Dewantara Ananda Putra; Indra Mulyawan; Aris Setyawan (Majalah Biomorfologi, 2024)
Highlights Smoking is a notable and extensively debated risk factor for problems following tooth extraction, but research on electronic cigarettes remains scarce. Electronic cigarettes contain various components comparable with those in conventional cigarettes, potentially resulting in similar chemical composition and effects on alveolar osteitis.   Abstract Background: Tooth extraction is one of the minor dental surgical procedures involving the hard and soft tissues of the oral cavity and has several possible complications. One potential risk is alveolar osteitis, also known as dry socket, which is an inflammation marked by intense pain and the dislodging of the blood clot. Smoking behavior is a significant risk factor for alveolar osteitis. Objective: This article aimed to analyze the effect of smoking and electronic cigarette ingredients on the incidence of alveolar osteitis after tooth extraction. Material and Methods: This research was conducted as a scoping review by performing thorough search of the PubMed, Scopus, ScienceDirect, and Google Scholar databases. Research published between 2013 and August 2023 in English language were assessed in this review. Result: A total of ten papers have been included in the analysis. Comparative studies consistently demonstrated that individuals who engage in smoking are at a significantly elevated risk of developing alveolar osteitis following tooth extraction. Discussion: Both conventional and electronic cigarettes can dislodge the blood clot that forms at the tooth socket after tooth extraction as a result of the sucking movement involved in smoking. Electronic cigarette components reduce oxygen delivery to healing tissues, hence accelerating fibrinolysis. Conclusion: Electronic cigarettes affect the occurrence of alveolar osteitis by the act of smoke inhaling and the presence of substances like carbon monoxide and nicotine.